Halal Certification, Brand Image, dan Celebrity Endorse: A Study on Zoya Hijab's Consumers - Hayati, Safaah Restuning; Pramesti, Dwi Meilina Siwi (DINIKA : Academic Journal of Islamic Studies, 2021)
Zoya is one of the Muslim clothing companies with halal certification from the authorized institution, MUI (The Council of Indonesian Ulama). This study aimed to determine the effect of halal certification, brand image, and celebrity endorser on Zoya hijab purchasing decisions. This study used incidental sampling technique conducted in the city of Yogyakarta. The data analysis technique used Partial Least Square (PLS), which consists of outer model and inner model tests. The outer model test is divided into two tests: the validity test and reliability test and the inner model test consists of two kinds of tests, namely the R test and the Gof test. The results of the analysis of this study revealed that the variables of halal certification (X1), brand image (X2) and celebrity endorser (X3) have a positive and significant effect on purchasing decisions (Y) of Zoya hijab in Yogyakarta. The results of the R Square test obtained a value of 73%. This means that halal certification, brand image, and celebrity endorser have a strong contribution to the consumers' purchasing decision on Zoya hijab. Halal certification provides an assurance and a guarantee for the quality of a product. This is because the halal label on a product means that the product has been rated thayyib (wholesome).